- “Pemidanaan Oleh Hakim Dalam Pencurian Pada Malam Hari Di Rumah (Putusan Nomor 638/ Pid. B/ 2020/ PN MRE)”: - - Diastika Fajar Anggraeni; Maria Silvya E. Wangga (Reformasi Hukum Trisakti, 2023)
Regarding nighttime stealing at home, decision number 638/Pid.B/2020/PN MRE was made. In Decision Number 638/Pid.B/2020/PN MRE, the issue is whether the author's actions are in accordance with Article 363 paragraphs (1), fourth and fifth, of the Criminal Code, and what sentencing guidelines the judge took into account when imposing a decision on the case. Legal research, which is descriptive analysis in nature, is the research methodology used. This study's findings and debate led to the development of sentencing recommendations and goals. The conclusion of this study is that the judge's judgment is asynchronous when employing the requirements of Article 363 paragraphs (1) 4 and 5 of the Criminal Code and sentencing standards that are considered by judges in applying criminal sanctions to perpetrators must be objective so that later the judge will fully fulfill the goals of security and justice. The conclusion of this study: the defendant's actions in this case do not meet the requirements of Article 363 paragraph (1) 5, but the requirements of Article 363 paragraph (2) of the Criminal Code and the sentencing guidelines used are evidence, legal facts, witness statements from victims, and statements from the accused. These sentencing guidelines have not yet been regulated in the Criminal Code and have only been found in the 2019 Draft Criminal Code.